Analisis Produktivitas Kegiatan Bongkar Muat Pada Kapal-Kapal Pelni Oleh PT. Sarana Bandar Nasional Di Pelabuhan Tanjung Priok - Fauzia, Rizka; Bijaksana, Gena; Bimarso, Wahyono (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of this research is to analyze the loading and unloading activities on Pelni ships and the relationship of ship loading and unloading productivity to the ship berthing time on Pelni ships by PT SBN at Tanjung Priok Port. This research method uses quantitative analysis, where the data obtained are company data analysis technique used is simple linear regression analysis using SPSS version 25 software. The results of this study state that loading and unloading productivity in 2020 and 2021 has the highest average, 12 Teus/Gang/Hour. The longest time for ships to berth in 2020 is 25.36 hours, and in 2021 the longest time for ships to berth is 23.06 hours. From the calculation result of simple regression show that there is a positive relationship between loading and unloading productivity and the time the ship is thetered. After testing the hypothesis, there is a significant relationship between loading and unloading productivity (Variable X) and berthing time (Variable Y). However, the productivity of loading and unloading and the time of berthing still need to be considered and improved to produce maximum results and the company does not suffer losses or decrease in quality.